KOMODIFIKASI PEKERJA DI LEMBAGA PENYIARAN PUBLIK TVRI BENGKULU - Sindy Amalia Putri; Anis Endang SM (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
TVRI Bengkulu Public Broadcasting Institution (LPP) which is supposed to be responsible for the welfare of its workers, especially freelancers, is more concerned with the workload of its workers because a person's workload must be appropriate and balanced against the physical and psychological abilities of workers. This study aims to determine the commoditization of workers carried out on TVRI Bengkulu television station. This research method uses qualitative research methods which are presented descriptively. Informants in this study used purposive sampling, namely Kasubsi TVRI Bengkulu Program, Journalists, News Administration, News Broadcasters, and employees who had worked at TVRI Bengkulu from various fields such as Journalists, Production Engineering, and Program Staff. Methods of collecting data using observation, in-depth interviews, and documentation. Data analysis techniques use the method of constant cooperative technique. Based on the results of the study, it can be seen that the occurrence of Commoditization of Workers in the TVRI Bengkulu Public Broadcasting Institution is true, this is indicated by the existence of work inequality ranging from additional work to the salary system obtained. When referring to the theory put forward by Vincent Mosco the media make optimal use of energy and mind by forcing them to do more than one job as a form of employee loyalty to the media industry.